PELATIHAN KETERAMPILAN PROSES ILMIAH BERBASIS ORGANISASI BELAJAR BAGI GURU SEKOLAH DASA - Sarwanto, Sarwanto; Hinduan, Achmad; Trisnamansyah, Sutaryat; Rusli, A (Universitas Sebelas Maret, 2009)
This research aims to investigate the effectiveness of training in scientific process skills for elementary schoolteachers based on the learning organization in improving their professionalism. The scientific training based on learning organization was developed using systematic approach. This approach was in line with the school as anorganizationthatshouldproducelearners.Alearningorganizationisanorganization whose members are sensitive to problems, to overcome problems together and continuously, and to reach target that have been specified. The research method in this study was a modification of the Borg & Gall (1979) Research & Development (R&D) method. This research was done in Wonogiri regency and 34 teachers were involved. Principally, this research used a design one-group-pretest-posttest to determine the effectiveness of the research subject treatment. Based on the study, it can be concluded that the training model based on the learning organization can significantly improve the mastery of the concept, the skill processes and the ability of science learning. This training is supported by supervisor and head-masters, so it can be followed-up by the teacher activities team (KKG) in the classroom. Finally, it can be recommended that: (1) the training system based on the learning organization can be used to enhance school independence in improving the teachers' professionalism; (2) sources of learning available in school require to motivate teacher in training activity; (3) training of science teaching is better done step by step in order to run well; (4) headmaster and supervisor involved in socializationshouldsupportthetrainingactivitytotally.